Myanmar Investment Climate Assessment : Sustaining Reforms in a Time of Transition - World Bank Group (Washington, DC, 2015)
This is the first investment climate assessment (ICA) for Myanmar. The main objectives of this ICA are to: (i) provide an up-to-date and fact-based analysis of the business environment for the government and other stakeholders in Myanmar to help prioritize and contextualize the reform agenda, and (ii) to offer a baseline for future assessments of progress in terms of the investment climate reform agenda. As requested by the government, the Myanmar ICA will directly support the ongoing reform program. The government has requested an analytical foundation for the ongoing reform program, and a means for prioritizing the legal and institutional changes that are currently being initiated. This ICA is based on the 2014 Myanmar enterprise survey (ES). The Myanmar ICA provides a comprehensive analysis of the country's ES. The ES in Myanmar was carried out between February and April 2014, although significant work preceded and followed the survey itself. This ICA report is organized into four chapters. The first chapter provides an introduction into the context of Myanmar's challenges in terms of the overall economy and the investment climate in particular. The second chapter analyzes the main constraints faced by firms operating in Myanmar today, in particular the constrained access to inputs like finance, land, electricity, and skilled workers. The third chapter looks at policies the government has in place for overseeing the economy, such as firm regulations and taxation. The fourth and concluding chapter provides policy recommendations that follow from the analysis, in terms of the process of reform and the specific reform steps needed over the short and medium terms. The annex to this report provides details on the methodology of the ES.